2014
DOI: 10.1093/nar/gku156
|View full text |Cite
|
Sign up to set email alerts
|

fourSig: a method for determining chromosomal interactions in 4C-Seq data

Abstract: The ability to correlate chromosome conformation and gene expression gives a great deal of information regarding the strategies used by a cell to properly regulate gene activity. 4C-Seq is a relatively new and increasingly popular technology where the set of genomic interactions generated by a single point in the genome can be determined. 4C-Seq experiments generate large, complicated data sets and it is imperative that signal is properly distinguished from noise. Currently, there are a limited number of metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 43 publications
0
56
0
Order By: Relevance
“…It uses BAM alignment files as input, and performs aligned reads counting, read count normalization, statistical analysis of interactions and data visualization or data export of contacting regionsHiTCServant, 2012 [130]R package. It allows the use of both 5C and Hi-C data and offers quality control, normalization and visualization of heatmapsfourSigWilliams, 2014 [131]R package. Includes fragment filtering optionsBasic4CseqWalter, 2014 [132]R package.…”
Section: Bioinformatics Challengesmentioning
confidence: 99%
“…It uses BAM alignment files as input, and performs aligned reads counting, read count normalization, statistical analysis of interactions and data visualization or data export of contacting regionsHiTCServant, 2012 [130]R package. It allows the use of both 5C and Hi-C data and offers quality control, normalization and visualization of heatmapsfourSigWilliams, 2014 [131]R package. Includes fragment filtering optionsBasic4CseqWalter, 2014 [132]R package.…”
Section: Bioinformatics Challengesmentioning
confidence: 99%
“…The methods used for statistical analysis are detailed elsewhere (WILLIAMS JR. et al 2014), though they are based upon previously published methods (SPLINTER et al 2011). What follows is a basic outline of our method.…”
Section: Statistical Analysis Of Mapped Readsmentioning
confidence: 99%
“…To deal with this issue some of the available pipelines transform the data to a binary signal (a score of zero or one) based on the presence or absence of a read at each restriction enzyme fragment[6, 11, 12]. To investigate the extent of the PCR amplification bias a recent study incorporated random barcodes in their experimental strategy and found no selective bias in their usage[13]. This demonstrates that binary transformation removes information that can be obtained from the number of captured interactions at a given restriction enzyme fragment.…”
mentioning
confidence: 99%
“…To account for this, a genomic window is typically used to analyze interactions as opposed to dealing with individual fragments. [6, 11, 13, 15]. However, it should be noted that the use of arbitrary window sizes may obscure the boundary of interacting domains that can be detected so it is important to first determine the appropriate size.…”
mentioning
confidence: 99%